Retention and Attrition in U.S. STEM Education with the Help of Computer Technology and Curriculum Development - Esfahani, Mahshad Nasr; Bhattacharya, Subhasankar (International Journal of Scientific Research and Management (IJSRM), 2023)
This article explores the pressing issue of retention and attrition in STEM (Science, Technology, Engineering, and Mathematics) education in the United States, focusing on the role of computer technology and curriculum development in improving retention rates. The study examines factors contributing to student persistence and attrition, including gender and racial disparities, and the impact of first-year experiences. It also delves into the evolution of educational technology, such as online learning platforms, virtual and augmented reality, and learning analytics, and their influence on student engagement and retention. The role of curriculum innovations, such as active learning, project-based learning, and interdisciplinary approaches, is analyzed to highlight effective strategies for retaining students in STEM fields. Through a mixed-methods research design, including quantitative and qualitative data collection, the study presents findings on the effectiveness of technological and curricular interventions, offering recommendations for policy and best practices to enhance STEM education in the U.S.